Prevention of Mitral Ring Dehiscence by a Simple Modification of Suture Placement - Makarious Laham, Majd; Easo, Jerry; Roosta-Azad, Mehdy; Kamler, Markus (The Thoracic and Cardiovascular Surgeon, 2023)
Ring dehiscence is a serious complication after mitral valve annuloplasty, tending to occur primarily from the posterior annulus. The tension on the ring sutures during the cardiac cycle is one of the suspected reasons; to minimize this tension, we apply four additional pledgeted sutures positioned supra-annularly at critical hinge points and could achieve a marked reduction of annular dehiscence since.
Keywords: mitral valve; surgery; surgical techniques